The Un-Americans Jews, the Blacklist, and Stoolpigeon Culture - Litvak, Joseph (Duke University Press, 2009)
In a bold rethinking of the Hollywood blacklist and McCarthyite America, Joseph Litvak reveals a political regime that did not end with the 1950s or even with the Cold War: a regime of compulsory sycophancy, in which the good citizen is an informer, ready to denounce anyone who will not play the part of the earnest, patriotic American. While many scholars have noted the anti-Semitism underlying the House Un-American Activities Committee's (HUAC's) anti-Communism, Litvak draws on the work of Theodor W. Adorno, Hannah Arendt, Alain Badiou, and Max Horkheimer to show how the committee conflated Jewishness with what he calls "comic cosmopolitanism," an intolerably seductive happiness, centered in Hollywood and New York, in show business and intellectual circles. He maintains that HUAC took the comic irreverence of the "uncooperative" witnesses as a crime against an American identity based on self-repudiation and the willingness to "name names".